2013
DOI: 10.1155/2013/423407
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effect of Natural Anti-Inflammatory Compounds on Cytokines Released by Chronic Venous Disease Patient-Derived Endothelial Cells

Abstract: Large vein endothelium plays important roles in clinical diseases such as chronic venous disease (CVD) and thrombosis; thus to characterize CVD vein endothelial cells (VEC) has a strategic role in identifying specific therapeutic targets. On these bases we evaluated the effect of the natural anti-inflammatory compounds α-Lipoic acid and Ginkgoselect phytosome on cytokines/chemokines released by CVD patient-derived VEC. For this purpose, we characterized the levels of a panel of cytokines/chemokines (n = 31) in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 37 publications
(38 reference statements)
1
30
0
1
Order By: Relevance
“…Thus, more studies are needed to establish if oxidative stress is the cause or the consequence of therapeutic properties of G. biloba extracts. For instance, G. biloba extracts have antiinflammatory properties in different in vitro and in vivo models (Apetz et al, 2014;Siegel et al, 2014;Tisato et al, 2013;Chen et al, 2014;Hirata et al, 2015) and the inhibition of inflammatory response can decrease the oxidative stress. In short, the complex interplay between primary cellular responses and oxidative stress in chronic degenerative diseases and the modulation of this interaction by plant extracts need more detailed studies.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, more studies are needed to establish if oxidative stress is the cause or the consequence of therapeutic properties of G. biloba extracts. For instance, G. biloba extracts have antiinflammatory properties in different in vitro and in vivo models (Apetz et al, 2014;Siegel et al, 2014;Tisato et al, 2013;Chen et al, 2014;Hirata et al, 2015) and the inhibition of inflammatory response can decrease the oxidative stress. In short, the complex interplay between primary cellular responses and oxidative stress in chronic degenerative diseases and the modulation of this interaction by plant extracts need more detailed studies.…”
Section: Resultsmentioning
confidence: 99%
“…In a previous study Leucoselect ® Phytosome ® has been proven able to reduce oxidative stress [4] while some reports suggested a protective effect of α-Lipoic acid on endothelial cell damage [5] and antioxidant proprieties [6]. In particular, the alpha-lipoic acid plays cytoprotective action against free radicals [6,11], especially protecting the nerves in the case of induced degeneration (itching / paresthesia symptomatology). The leucocianidine (Leucoselect) shows an activity of reducing vascular permeability, savings of vitamin E, chelation of iron and copper, inhibition of protease (hyaluronidase, collagenase, elastase).…”
Section: Discussionmentioning
confidence: 99%
“…Ginkgo-biloba performs a regulating action on the arterial tone and increase in capillary permeability (increased nitric oxide concentration), therefore it provides vasoprotective action both on venules and arterioles [12]. Furthermore, it has been shown that the synergic use of α-lipoc acid, Leucoselect ® and Ginkgoselect ® phytosome is accompanied by an improvement in the levels of numerous cytokines and factors involved in inflammation [11,13].…”
Section: Discussionmentioning
confidence: 99%
“…Our study showed that GBE had no effect on aortic dilation in AngII-induced AAAs, but it prevented aortic rupture. There are reports that GBE protects against endothelial dysfunction [22], inflammation [23], and MMP expression [13]. Platelets deposition has also been found in human AAAs tissue, and clopidogrel, a platelet P2Y12 receptor inhibitor, suppresses the development of AngII-induced AAAs [24].…”
Section: Discussionmentioning
confidence: 99%